2013
DOI: 10.1002/jgrc.20326
|View full text |Cite
|
Sign up to set email alerts
|

Forcing mechanisms of heat content variations in the Yellow Sea

Abstract: Forcing mechanisms of heat content variations in the Yellow Sea (YS) are studied through analysis of a hindcast simulator for 1958–2007 using a two–way nested global—Northwest Pacific model. During the cooling season (September to February of next year), changes in heat content integrated over the YS are primarily caused by variations in latent and sensible heat fluxes at surface, which can be further related to variations of the East Asian Winter Monsoon and the Arctic Oscillation. The lateral heat transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The YSWC, as the only external heat source in the eastern China Sea, contributes to the variation in heat content in the SYS. The heat transported by the YSWC in winter is five times smaller than that of the net surface heat loss integrated over the Yellow Sea (Wei et al, 2013). The winter SST is inversely and weakly correlated with the EAWM indices and short-wave radiation, respectively (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The YSWC, as the only external heat source in the eastern China Sea, contributes to the variation in heat content in the SYS. The heat transported by the YSWC in winter is five times smaller than that of the net surface heat loss integrated over the Yellow Sea (Wei et al, 2013). The winter SST is inversely and weakly correlated with the EAWM indices and short-wave radiation, respectively (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By adopting OTPS(OSU tidal prediction software), model open boundary drives based on the real time water level of eight primary tidal predication, which is M2, S2, N2, K2, K1, O1, P1 and Q1. The temperature and salinity data in open boundary adopt the data of NEMO2.3 (nucleus of European modeling of the ocean) [10] . Initial conditions of temperature and salinity adopt data of WOA09 (world ocean atlas 2009).…”
Section: Model Configuration and Sensitivity Experimentsmentioning
confidence: 99%
“…With the seasonal change of the thermocline, the YSCWM forms in the spring (approximately in May), matures in the summer (approximately in August), recedes in the autumn, and completely disappears in winter (Guan, 1963;Chu et al, 1997;Yu et al, 2006;Zhang et al, 2008;Bao et al, 2009;Yao et al, 2012). During the cooler season (from September to February), changes in the heat content of the YS are caused by variations in latent and sensible heat fl uxes at the surface, which are related to the East Asian Winter Monsoon and the Arctic Oscillation (Wei et al, 2013). In the early 1950s, He et al (1959) fi rst studied the formation mechanism and characteristics of the YSCWM concluding that the YSCWM forms in the local area of the YS in winter.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, winter process plays an important role in the interannual variability of the YSCWM. Wei et al (2013) found that the heat content of the deep region of the YS is mainly infl uenced by lateral heat transport controlled by the Yellow Sea Warm Current (YSWC), which also has a 4-7-year period of interannual variability .…”
Section: Introductionmentioning
confidence: 99%